O processo de implementação do terceiro ciclo para as aprendizagens: concepções docentes - Chagas, Alisson Moura (2019)
This research is part of the research line "Education Policy, Management and Evaluation" of the Graduate Program in Education of the Catholic University of Brasilia (UCB). The general objective of the research is to investigate the implementation of the third cycle for the learning in the schools of the Public Education Network of the Federal District. Having as specific objectives: to contextualize the educational legislation with regard to the school organization (in cycles for the learning); to characterize / discriminate the school organization through the use of cycles for learning in the Public Education Network of the Federal District; to examine the implementation of the 3rd cycle for the learning in a Center of Elementary School belonging to the Regional Teaching Coordination (CRE) of Samambaia from the conceptions of the teachers. It is a qualitative research with methodological procedures of documentary, bibliographical and empirical research. The documentary analysis was composed by the study of the legal documents: the Law of Directives and Bases of National Education (LDB), nº 9394 of 1996, which makes possible the cyclized organization for Elementary Education of 9 (nine) years, Law 13.005, of June 25, 2014, which approves the National Education Plan from 2014 to 2024 (PNE) that addresses the goals and strategies for education in a period of 10 (ten) years. Law No. 5.499, of July 14, 2015, which approves the District Education Plan (PDE). The Pedagogical Guidelines for the Organization of the 3rd Cycle for Learning published in 2014, in addition to the documents that guide the district curriculum. In the bibliographical research, the authors who research on educational public policies that deal with the organization of teaching are used as theoretical support. The theoretical foundations of Mainardes (2009), Freitas (2003), Ball and Mainardes (2011), Gomes (2011) Arroyo (1999), among others authors who refer to the thematic of pedagogical organization in cycles will compose the theoretical framework in this work. In the last stage, the empirical research was carried out from semistructured interviews with teachers from the State Department and Education of the Federal District (SEEDF), for at least two years and at the Central Education Center (CEF) 120 of the Administrative Region (RA) from Samambaia to analyze teachers' conceptions in the process of implementing cycles for learning in SEEDF. The main results indicate that the process of school organization must be implemented with caution, since the legislation is the basis of this public policy, but the laws do not support it alone. The data analyzed indicate the concern of the teachers with student retention, as well as the continuous training to act in the cycles, since it is not enough to change the form of organization of schooling, it is necessary to use the teachers so that they can materialize the policy in the classrooms.